Parochial Structure and the Dissemination of Protestantism in Sixteenth Century England: A Tale of two Cities - Cross, Claire (Studies in church history, 1979)
When, after the abrupt changes in religion in the reigns of Henry VIII, Edward VI and Mary, Elizabethan protestants set about consolidating the protestant reformation they looked upon towns as one of the chief agencies for the conversion of the countryside. From the first moment of his appointment as lord president of the council in the north in 1572 that enthusiastic layman, the third earl of Huntingdon, made this assumption a guiding principle of his governorship. ‘I do all I can to get good preachers planted in the market towns of this country’, he told William Chaderton, bishop of Chester in 1584, adding with a characteristic note of realism, ‘in which somewhat is already done, but much remaineth to be done.’ Huntingdon’s close associate and fellow worker in the north, archbishop Grindal, had earlier informed the queen in similar terms that ‘the continual preaching of God’s word in Halifax’ in the 1560s had been responsible for the town’s stalwart loyalty to the crown during the Rebellion of the Earls. Yet both Grindal and Huntingdon knew very well from personal experience that towns in general and northern towns in particular had not by any means all accorded an automatic or unqualified welcome to protestantism. A comparison between York and Hull demonstrates forcefully how two towns in close geographical proximity could differ very considerably in their initial acceptance of protestantism and in the readiness of their ruling élites to further the propagation of protestant doctrines among the townspeople at large.